The war in Ukraine and the growing North-South divide: a European Union perspective - Ekman, Alice (2023)
In Europe, a strong consensus exists around the condemnation of Russia’s invasion of Ukraine, and it was expected that such consensus would naturally broaden globally. In fact, this is not the case. A North-South divide has emerged on this issue, partly due to the position of China, which has consolidated its partnership with Russia, and a clear anti-West strategy is apparent.